Analisis Pertimbangan Hukum Kasus Kartel Minyak Goreng Di Indonesia - Yuniar Hayu Wintansari (Lex Renaissance, 2020)
This study was conducted to determine the appropriate legal considerations in the cooking oil cartel case between the Business Competition Supervisory Commission (KPPU), the District Court, and the Supreme Court. This is a normative legal research that uses statutory approach and case study. This study concludes that according to legal provisions or legal certainty in force in Indonesia, the legal considerations of the District Court are in accordance with thie principle in the cooking oil cartel case because indirect or intuitive evidence cannot be used in competition law in Indonesia. However, if it is based on the principles of justice and expediency, then the KPPU's legal considerations hence become more appropriate because KPPU has treated the wider community who have been harmed by the price of cooking oil.